Pohozhaev and Morawetz Identities in Elastostatics and Elastodynamics - Bozhkov, Y.; Olver, P.J. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
We construct identities of Pohozhaev type, in the context of elastostatics and elastodynamics, by using the Noetherian approach. As an application, a non-existence result for forced semi-linear isotropic and anisotropic elastic systems is established.